The Use of Removed Mesquite Brush as a Fiber Replacement in Silage Production - William Taylor Fair; Jeffrey Bryan Breeden; Thomas Wayne Atchley; Barry Don Lambert; Zhan Aljoe; Walter Franklin Owsley; William Brandon Smith (Animals, 2022)
Mesquite (Prosopis L.) is considered an invasive browse species in most of the American Southwest. Mechanical intervention removes yields an excess of organic debris. Anecdotal evidence in the past has supported using such browse as feed for livestock. Thus, our objectives were to (1) determine the nutritive value and fermentation characteristics of silage produced with mesquite biomass, and (2) evaluate solvent treatment of mesquite biomass prior to ensiling. In Experiment 1, we evaluated mesquite inclusion rate (0, 250, 500, 750, or 1000 g kg−1 DM), length of fermentation (28, 56, or 84 d), and silage inoculant. In Experiment 2, we evaluated the effects of mesquite pre-treatment with acid (H2SO4) or alkali (NaOH) solutions. Concentrations of NDF, ADF, and ADL, as well as IVTD, decreased (p < 0.05) with increasing mesquite inclusion. However, 250 g mesquite kg−1 DM did not differ from grass silage. There was no effect (p > 0.05) of inoculation, though increasing length of incubation did increase (p < 0.05) VFA production and decrease (p < 0.05) silage pH. Solvent treatment did not improve ensiling properties. Results are interpreted to mean that mesquite biomass may be effectively incorporated into silage at levels up to 250 g kg−1.